PENERAPAN PEMBELAJARAN BERBASIS ICT UNTUK MENINGKATKAN PRESTASI BELAJAR MATA PELAJARAN SOSIOLOGI PADA SISWA KELAS X7 SMA NEGERI 3 SURAKARTA TAHUN PELAJARAN 2012/2013 - Devy Permatasari, Mike (SOSIALITAS; Jurnal Ilmiah Pend. Sos Ant)
Mike Devy Permatasari. K8409039. ICT BASED LEARNING APPLICATION FOR IMPROVING LEARNING ACHIEVEMENT IN SOCIOLOGY SUBJECT CLASS X7 SMA NEGERI 3 SURAKARTA SCHOOL YEAR 2012/2013. Thesis, Surakarta: Faculty of Teacher Training and Education. Sebelas Maret University of Surakarta, June 2013. This study aims to improve and enhance student achievement through the implementation of ICT based learning in the subjects of sociology. Type of research is a classroom action research with subjects X7 grade students of SMA Negeri 3 Surakarta academic year 2012/2013 which consisted of 33 students. The experiment was conducted in two cycles of action. Discuss the subject of the first cycle and second cycle of Social Deviation and Social Control. The data were obtained from the results of sociological observation during learning activities take place by using observation sheets, records of activities, and documentation. The results showed that the X7-class student achievement SMA Negeri 3 Surakarta on sociological subjects have increased after the implementation of ICT-based learning. This is indicated by an increase in average student learning outcomes in each cycle. Average student learning outcomes before the action amounted to 67.82, after the first cycle the action applied to the average student learning outcomes increased by 8.88 to 76.70. In the second cycle the average student learning outcomes increased to 85. Conclusion this research is the application of ICT based learning can improve learning achievement sociology subjects in grade X7 SMA Negeri 3 Surakarta. Keywords: Pembelajaran, ICT, Prestasi Belajar